A method for online verification of adapted fields using an independent dose monitor. Issue 7 (21st June 2013) - Chang, Jina; Heaton, Robert K.; Mahon, Robert; Norrlinger, Bernhard D.; Jaffray, David A.; Cho, Young‐Bin; Islam, Mohammad K.
Abstract : Purpose: : Clinical implementation of online adaptive radiotherapy requires generation of modified fields and a method of dosimetric verification in a short time. We present a method of treatment field modification to account for patient setup error, and an online method of verification using an independent monitoring system. Methods: : The fields are modified by translating each multileaf collimator (MLC) defined aperture in the direction of the patient setup error, and magnifying to account for distance variation to the marked isocentre. A modified version of a previously reported online beam monitoring system, the integral quality monitoring (IQM) system, was investigated for validation of adapted fields. The system consists of a large area ion‐chamber with a spatial gradient in electrode separation to provide a spatially sensitive signal for each beam segment, mounted below the MLC, and a calculation algorithm to predict the signal. IMRT plans of ten prostate patients have been modified in response to six randomly chosen setup errors in three orthogonal directions. Results: : A total of approximately 49 beams for the modified fields were verified by the IQM system, of which 97% of measured IQM signal agree with the predicted value to within 2%. Conclusions: : The modified IQM system was found to be suitable for online verification of adapted treatment fields.